PENGARUH PERBEDAAN JENIS IKAN TERHADAP PERTUMBUHAN IKAN DALAM SISTEM BUDIDAYA DALAM EMBER (BUDIDAMBER) - Sogen, Katharina Desembrianty Prianka; Salosso, Yuliana; Pasaribu, Wesly (Hasanuddin University, 2025)
This study aims to analyze the effect of different fish species on fish growth in a bucket aquaculture system (Budidamber). The study was conducted from July to September 2024 at the Dry Land Aquaculture Laboratory, Nusa Cendana University, Kupang, using 60 catfish (Clarias gariepinus), 60 tilapia (Oreochromis niloticus), and 60 patin fish (Pangasius sp.) with an average weight of ±10 grams and an average length of ±8 cm. The study used a completely randomized design (CRD) with three types of treatments, each repeated three times. The treatments were A (catfish), B (tilapia), and C (pangasius). The parameters observed included absolute weight gain, absolute length gain, and fish survival. The results of the analysis showed that the catfish treatment had a significant effect (P<0.05) on absolute weight gain. However, for the parameters of length increase and survival, no significant differences were found (P>0.05) between the three types of fish.